2021
DOI: 10.1021/acs.nanolett.1c02416
|View full text |Cite
|
Sign up to set email alerts
|

Inside the Protein Corona: From Binding Parameters to Unstained Hard and Soft Coronas Visualization

Abstract: Proteins spontaneously adsorb on nanoparticle surfaces when injected into the bloodstream. It drastically modifies the nanoparticle's fate and how they interact with organs and cells. Although this protein layer (protein corona) has been widely studied, the robustness of the most employed characterization methods and the visualization of its unstained fractions remain open questions. Here, synchrotron-based small-angle X-ray scattering was used to follow the corona formation and estimate binding parameters. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 54 publications
3
22
0
Order By: Relevance
“…The formation of a BSA corona on silica NPs was studied by other groups and seems to be size-dependent. A corona thickness of 7 nm and 4 nm was reported by Galdino et al for 40 nm and 80 nm -silica NPs respectively [17]. Monopoli et al observed a corona thickness of 4 nm for 200 nm silica NPs [27].…”
Section: Measuring the Protein Corona Thicknessmentioning
confidence: 82%
See 3 more Smart Citations
“…The formation of a BSA corona on silica NPs was studied by other groups and seems to be size-dependent. A corona thickness of 7 nm and 4 nm was reported by Galdino et al for 40 nm and 80 nm -silica NPs respectively [17]. Monopoli et al observed a corona thickness of 4 nm for 200 nm silica NPs [27].…”
Section: Measuring the Protein Corona Thicknessmentioning
confidence: 82%
“…Based on microscopy data, this was attributed by Galdino et al to the formation of small aggregates [17]. As TDA experiments showed that FET aggregation did not occur in phosphate buffer using such a concentration (see Supplementary material, section 2), NPs aggregation mediated by proteins might be considered, even if the formation of protein multilayers cannot be excluded in the absence of additional proofs.…”
Section: Measuring the Protein Corona Thicknessmentioning
confidence: 98%
See 2 more Smart Citations
“…This strategy validates the applicability of TEM methodologies to decipher fundamental PC aspects and its behavior in simple and complex media, which can contribute to rational design of nanomedicines. 69 Ptychographic X-ray computed tomography (PXCT) is an extension of X-ray imaging technique to perform non-invasive and lens-free imaging of protein structures at the membrane interface with quantitative electron density contrast at sharp resolutions of 15 nm, 70 which can be used to interpret PC and nano–bio interactions at the nanoscale level. Biological samples (tissue, organelle) are processed and prepared for cryo X-ray imaging (with a potential penetration of 100 nm thickness across the sample).…”
Section: Sr-based Techniques At Np–corona Interactionsmentioning
confidence: 99%